2014
DOI: 10.1371/journal.pone.0100078
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Streptomycin Resistance-Conferring Mutations in Mycobacterium tuberculosis Clinical Isolates from Poland

Abstract: Currently, mutations in three genes, namely rrs, rpsL, and gidB, encoding 16S rRNA, ribosomal protein S12, and 16S rRNA-specific methyltransferase, respectively, are considered to be involved in conferring resistance to streptomycin (STR) in Mycobacterium tuberculosis. The aim of this study was to investigate the spectrum and frequency of these mutations in M. tuberculosis clinical isolates, both resistant and susceptible to STR. Sixty-four M. tuberculosis isolates recovered from as many TB patients from Polan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 36 publications
6
43
1
3
Order By: Relevance
“…Interestingly, the majority of SM-resistant isolates in this study were identified either as MDR or showed resistance to more than one drug. Therefore, resistance to SM could be a diagnostic marker for polydrug resistance and MDR as described previously [3,8]. Double mutation both at rrs and rpsL genes has rarely been reported [3,28].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the majority of SM-resistant isolates in this study were identified either as MDR or showed resistance to more than one drug. Therefore, resistance to SM could be a diagnostic marker for polydrug resistance and MDR as described previously [3,8]. Double mutation both at rrs and rpsL genes has rarely been reported [3,28].…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, high rates of SM resistance and the risk of toxicity led to a gradual decline in the use of SM. However, SM continues to be an integral part of chemotherapy for TB either in combination therapy or as the first-line agent for cases still susceptible to aminoglycosides [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies‚ mutations in rpsL gene were likely to be associated with a high-level of STR resistance, whereas mutations in rrs gene were shown to confer to an intermediate-level, and in gidB gene a low-level of STR resistance [11,17,20,7,35,[38][39][40]. Mutations in rpsL, rrs and gidB genes were found in circa 70% of M. tuberculosis isolates that were resistant to STR [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in rpsL, rrs and gidB genes were found in circa 70% of M. tuberculosis isolates that were resistant to STR [21,23]. In the research investigating the three-gene panel (rrs, rpsL, and gidB genes), the proportions of STR-resistant isolates with wild-type alleles at all three loci were almost similar, i.e 11.8% in Korea [41], 12.5% in Sierra Leone [42], 6.9% in Vietnam [27], 22% in Brazil [30] and 12.5% in Poland [7]. The portions were much lower than all studies cited above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation